ANALISIS EKONOMI LINGKUNGAN TERHADAP PENGELOLAAN SAMPAH PERKOTAAN DI KOTA SEMARANG, JAWA TENGAH: IMPLIKASI BAGI PEMBANGUNAN BERKELANJUTAN - Muhammad Iqbal; Rosalina Kumalawati; Ellyn Normelani (Pelantar Press, 2023)
Rapid urbanization in Semarang City, Central Java, has increased solid waste generation and created challenges in sustainable waste management. This study aims to analyze urban waste management using the environmental economics perspective, emphasizing cost-benefit approaches, externalities, and community participation. The research method applies a qualitative-descriptive approach with literature review and secondary data analysis from government reports and academic journals. Results indicate that waste in Semarang reaches more than 1,200 tons per day, with only 70% transported to the Jatibarang landfill. Economic losses arise from unmanaged waste, including public health impacts, environmental degradation, and increased government expenditures. Applying environmental economics, such as the polluter pays principle, economic instruments for waste reduction, and community-based waste banks, can provide solutions. The findings highlight that strengthening policy integration, enhancing public participation, and adopting circular Ekonomi models are crucial for achieving sustainable development. This study contributes to the discourse on environmental policy and supports the design of local government strategies.